Neoplastic transformation induced by an activated lymphocyte-specific protein tyrosine kinase (pp56lck). - Marth, J D (1988)
The lck proto-oncogene encodes a lymphocyte-specific member of the src family of protein tyrosine kinases. Here we demonstrate that pp56lck is phosphorylated in vivo at a carboxy-terminal tyrosine residue (Tyr-505) analogous to Tyr-527 of pp60c-src. Substitution of phenylalanine for tyrosine at this position resulted in increased phosphorylation of a second tyrosine residue (Tyr-394) and was associated with an increase in apparent kinase activity. In addition, this single point mutation unmasked the oncogenic potential of pp56lck in NIH 3T3 cell transformation assays. Viewed in the context of similar results obtained with pp60c-src, it is likely that the enzymatic activity and transforming ability of all src-family protein tyrosine kinases can be regulated by carboxy-terminal tyrosine phosphorylation. We further demonstrate that overexpression of pp56lck in the murine T-cell lymphoma LSTRA as a result of a retroviral insertion event produces a kinase protein that despite wild-type primary structure is nevertheless hypophosphorylated at Tyr-505. Thus, control of normal growth in this lymphoid cell line may have been abrogated through acquisition of a posttranslationally activated version of pp56lck.